Isolation and identification of vibrio parahaemolyticus from flower crab (Portunus pelagicus) in Negeri Sembilan and Selangor / Nur Rabiatul Adawiah Mohammad Noor, Sahilah Abd. Mutalib and Norrakiah Abdullah Sani - Mohammad Noor, Nur Rabiatul Adawiah; Abd. Mutalib, Sahilah; Abdullah Sani, Norrakiah (2019)
This study was conducted to determine the presence of Vibrio parahaemolyticus on 30 samples of flower crab (Portunus pelagicus) collected from Negeri Sembilan (n = 15) and Selangor (n = 15) from March to July 2014. A total of 193 isolates of Vibrio sp. were isolated from the thiosulphate citrate bile-salt (TCBS) agar medium. Of 79 Vibrio isolates were identified as V. parahaemolyticus through biochemical testing methods. In V. parahaemolyticus identification by detection of regulatory gene toxR, 51 (64.6%) of 79 isolates contained toxR gene while none of the isolates contained virulence gene of tdh dan trh. by targeting toxR gene which produced amplicons of 368 bp molecular weight. All V. parahaemolyticus isolates were negative for tdh and trh genes.